2022
DOI: 10.5812/ijpbs-122958
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms, Anxiety, and Depression Among COVID-19 Survivors After Discharge from Hospital

Abstract: : The coronavirus disease 2019 (COVID-19) pandemic can lead to psychological issues; however, few studies have evaluated the mental health status of COVID-19 patients after discharge from the hospital. This study aimed to assess the psychological status of COVID-19 survivors and determine the risk factors associated with adverse psychological outcomes. Through a web-based cross-sectional survey, the data were collected from 158 COVID-19 survivors one month after discharge from the hospital using demographic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…The study revealed a high prevalence of mental health burden and COVID-19-related PTSD in participants with a positive history of psychiatric disorders (9). Another study also reported that people with psychiatric illnesses were more likely to exhibit higher levels of PTSD, depression, anxiety, and stress during the pandemic (19). Therefore, since outbreaks such as COVID-19 appear to cause a relapse or even worsen an existing mental disorder, it is essential to support this population.…”
Section: Discussionmentioning
confidence: 94%
“…The study revealed a high prevalence of mental health burden and COVID-19-related PTSD in participants with a positive history of psychiatric disorders (9). Another study also reported that people with psychiatric illnesses were more likely to exhibit higher levels of PTSD, depression, anxiety, and stress during the pandemic (19). Therefore, since outbreaks such as COVID-19 appear to cause a relapse or even worsen an existing mental disorder, it is essential to support this population.…”
Section: Discussionmentioning
confidence: 94%